Image of Hanuman in the Garbhagriha of the Maruti Temple - Mumbai Archive Project Team (Jio Institute, 2024)
A portrait of Sadhguru Narayan Maharaj (1885–1945), a spiritual teacher and guru, hangs next to the doorway (on the right) to the inner sanctum (garbagriha) at the Maruti Temple. Above the doorway is a painting of Lord Ganesh. On the left is a painting of Shri Ram, Shri Lakshman, and Devi Sita, with Lord Hanuman paying obeisance at their feet.